2019
DOI: 10.1111/1440-1630.12607
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the complexities of mild stroke: An interpretative phenomenological analysis of the mild stroke experience

Abstract: Introduction Limited research has been conducted from a longitudinal and qualitative perspective on the experience of life after mild stroke. This restricts the knowledge held in this area. This study aimed to answer the question: How do people with mild stroke understand their experiences in the first 6 months after hospital discharge? Methods Interpretative Phenomenological Analysis, involving five Australians with mild stroke, interviewed at 1‐, 3‐ and 6 months post‐hospital discharge. Results Two themes em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…This review revealed that stroke survivors' and caregivers' personal attributes and contextual factors played an important role in transitional care. Regardless of stroke severity, survivors' and caregivers' introspection triggered both negative and positive thoughts about stroke, their role, relationships with family and postdischarge life (Finch et al, 2020;Hodson et al, 2019). Survivors' and caregivers' prestroke family dynamics, past health conditions, willingness and readiness for caregiving shaped their ability to engage and participate in rehabilitation and discharge planning, and the development of self-management capacity (Chen et al, 2020;Hodson et al, 2019;Osborne, & Neville, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review revealed that stroke survivors' and caregivers' personal attributes and contextual factors played an important role in transitional care. Regardless of stroke severity, survivors' and caregivers' introspection triggered both negative and positive thoughts about stroke, their role, relationships with family and postdischarge life (Finch et al, 2020;Hodson et al, 2019). Survivors' and caregivers' prestroke family dynamics, past health conditions, willingness and readiness for caregiving shaped their ability to engage and participate in rehabilitation and discharge planning, and the development of self-management capacity (Chen et al, 2020;Hodson et al, 2019;Osborne, & Neville, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of stroke severity, survivors' and caregivers' introspection triggered both negative and positive thoughts about stroke, their role, relationships with family and postdischarge life (Finch et al, 2020;Hodson et al, 2019). Survivors' and caregivers' prestroke family dynamics, past health conditions, willingness and readiness for caregiving shaped their ability to engage and participate in rehabilitation and discharge planning, and the development of self-management capacity (Chen et al, 2020;Hodson et al, 2019;Osborne, & Neville, 2019). Moreover, it is estimated that 40% of stroke survivors experienced cognitive impairment that had a significant impact on their self-management capability, and this is associated with a higher level of caregiver burden (Sexton et al, 2019;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been widely used to explore the psychological and physical development of stroke survivors (Garcia‐Rudolph et al, 2022; Huang et al, 2021). Moreover, a longitudinal qualitative study found that 1 month, 3 months, and 6 months post‐discharge were key time points in the rehabilitation experience of stroke survivors (Hodson et al, 2019). Therefore, it is essential to explore the development of rumination during the rehabilitation process in young and middle‐aged stroke survivors using GMM at 1‐week pre‐discharge (T0), 1 month (T1), 3 months (T2), and 6 months (T3) post‐discharge.…”
Section: Introductionmentioning
confidence: 99%
“…These gaps can result in unmet psychosocial needs, which can impact quality of life and adherence to stroke risk-factor management strategies ( 11 ). Unmet psychosocial needs are particularly relevant for those with milder stroke, characterized by SS with limited impairments who may be discharged from the hospital ≤ 4 days post-stroke, and may receive minimal services post discharge ( 12 , 13 ). Recent medical advances in stroke care (e.g., mobile stroke units, thrombolysis, mechanical thrombectomy), which have been associated with reductions in stroke severity, will likely increase the prevalence of milder stroke ( 10 , 14 ).…”
Section: Introductionmentioning
confidence: 99%